Оптимизация режимов эксплуатации конденсаторов паровых турбин с учетом характеристик отложений в трубных пучках - Шелепов, И. Г.; Сафронюк, М. А. (НТУ "ХПИ", 2006)
Діагностика вакууму в конденсаторах в темпі процесу по виробленню електроенергії- одна з актуальних задач при експлуатації енергоблоків. Авторами показана можливість вдосконалення технічної діагностики поточного вакууму конденсатора, за рахунок уточнення величини термічного опору.

Diagnostics of vacuumin condensers in the rate of process on making of electric power is one of actual tasks during exploitation of power units. Authors show possibility of perfection of technical diagnostics of current vacuum of condenser, due to clarification of size of thermal resistance.
Optimization of the modes of exploitation of condensers of steam-turbines taking into account descriptions of deposits in pipe bunches
Keywords: вакуум; электроэнергия; энергоблоки; охлаждающая вода; турбоустановки; уравнения регрессии; водно-радиа-химическая лаборатория